Thioridazine inhibits autophagy and sensitizes glioblastoma cells to temozolomide. Issue 7 (11th December 2018) - Johannessen, Tor‐Christian; Hasan‐Olive, Md Mahdi; Zhu, Huaiyang; Denisova, Oxana; Grudic, Amra; Latif, Md Abdul; Saed, Halala; Varughese, Jobin K.; Røsland, Gro Vatne; Yang, Ning; Sundstrøm, Terje; Nordal, Anne; et al.
Abstract : Glioblastoma multiforme (GBM) has a poor prognosis with an overall survival of 14–15 months after surgery, radiation and chemotherapy using temozolomide (TMZ). A major problem is that the tumors acquire resistance to therapy. In an effort to improve the therapeutic efficacy of TMZ, we performed a genome‐wide RNA interference (RNAi) synthetic lethality screen to establish a functional gene signature for TMZ sensitivity in human GBM cells. We then queried the Connectivity Map database to search for drugs that would induce corresponding changes in gene expression. By this approach we identified several potential pharmacological sensitizers to TMZ, where the most potent drug was the established antipsychotic agent Thioridazine, which significantly improved TMZ sensitivity while not demonstrating any significant toxicity alone. Mechanistically, we show that the specific chemosensitizing effect of Thioridazine is mediated by impairing autophagy, thereby preventing adaptive metabolic alterations associated with TMZ resistance. Moreover, we demonstrate that Thioridazine inhibits late‐stage autophagy by impairing fusion between autophagosomes and lysosomes. Finally, Thioridazine in combination with TMZ significantly inhibits brain tumor growth in vivo, demonstrating the potential clinical benefits of compounds targeting the autophagy‐lysosome pathway. Our study emphasizes the feasibility of exploiting drug repurposing for the design of novel therapeutic strategies for GBM. Abstract : What's new? Resistance to Temozolomide (TMZ) is the main cause of treatment failure in patients with Glioblastoma Multiforme (GBM). Although controversial, the ability of TMZ to increase autophagy flux is believed to support cancer growth. The authors identified dopamine antagonist Thioridazine as a potent sensitizer of TMZ cytotoxicity acting through impairment of late‐stage autophagy in GBM cells. Thioridazine, combined with TMZ, inhibited tumor growth in vivo and increased survival in tumor‐bearing animals. This study demonstrates the feasibility of linking results from large‐scale genome‐wide RNAi studies with corresponding drug‐induced alterations in gene expression and underscores the therapeutic relevance of attenuating autophagy in GBM.